Outcome of urethral strictures treated by endoscopic urethrotomy and urethroplasty - Tinaut-Ranera, Javier; Arrabal-Polo, Miguel Angel; Merino-Salas, Sergio; Nogueras-Ocaña, Mercedes; Lopez-Leon, Victor; Palao-Yago, Francisco; Arrabal-Martin, Miguel; Lahoz-Garcia, Clara; Alaminos, Miguel; Zuluaga-Gomez, Armando (Canadian Urological Association Journal, 2014)
Introduction: We analyze the outcomes of patients with urethral stricture who underwent surgical treatment within the past 5 years. Methods: This is a retrospective study of male patients who underwent surgery for urethral stricture at our service from January 2008 to June 2012. We analyzed the comorbidities, type, length and location of the stricture and the surgical treatment outcome after endoscopic urethrotomy, urethroplasty or both. Results: In total, 45 patients with a mean age of 53.7 ± 16.7 years underwent surgical treatment for urethral stricture. Six months after surgery, 46.7% of the patients had a maximum urinary flow greater than 15 mL/s, whereas 87.3% of the patients exhibited no stricture by urethrography after the treatment. The success rate in the patients undergoing urethrotomy was 47.8% versus 86.4% in those undergoing urethroplasty (p = 0.01). Twenty percent of the patients in whom the initial urethrotomy had failed subsequently underwent urethroplasty, thereby increasing the treatment success. Conclusion: In most cases, the treatment of choice for urethral stricture should be urethroplasty. Previous treatment with urethrotomy does not appear to produce adverse effects that affect the outcome of a urethroplasty if urethrotomy failed, so urethrotomy may be indicated in patients with short strictures or in patients at high surgical risk.